2008
DOI: 10.1542/peds.2007-2461
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning in the First Year After Pediatric Traumatic Brain Injury

Abstract: Between 18% and 38% of the children with traumatic brain injury had significant executive dysfunction in the first year after injury, with greater dysfunction reported for children with more severe traumatic brain injury. Our findings support previous reports that preinjury learning and behavior problems, limited family resources, and poor family functioning adversely affect executive function. These results suggest a need for more systematic screening for executive dysfunction after traumatic brain injury to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 43 publications
6
83
1
2
Order By: Relevance
“…[6][7][8][9][10][11][12][13] In particular, executive dysfunction after pediatric TBI is associated with functional problems across home, school, and community settings both in the shortand long-term after injury. [6][7][8][9][10][14][15][16][17][18][19][20] Better treatment of executive dysfunction after injury may lead to improved functioning in everyday settings. 21 Problem-solving training has demonstrated promise in various clinical populations [22][23][24][25][26] ; however, it has only been preliminarily explored in pediatric TBI.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] In particular, executive dysfunction after pediatric TBI is associated with functional problems across home, school, and community settings both in the shortand long-term after injury. [6][7][8][9][10][14][15][16][17][18][19][20] Better treatment of executive dysfunction after injury may lead to improved functioning in everyday settings. 21 Problem-solving training has demonstrated promise in various clinical populations [22][23][24][25][26] ; however, it has only been preliminarily explored in pediatric TBI.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] In particular, executive dysfunction after pediatric TBI is associated with functional problems across home, school, and community settings both in the shortand long-term after injury. [6][7][8][9][10][14][15][16][17][18][19][20] Better treatment of executive dysfunction after injury may lead to improved functioning in everyday settings. 21 Problem-solving training has demonstrated promise in various clinical populations [22][23][24][25][26] ; however, it has only been preliminarily explored in pediatric TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in working memory is of particular interest in view of a previous report of poorer working memory in children with TBI compared with controls at 3 and 12 months after injury, indicating a special vulnerability of this skill to the effects of injury. 7 Future research will need to evaluate the longitudinal effects of an early intervention on longterm outcomes related to executive function.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the literature suggests that children experience decreased quality of life across cognitive, physical, and psychosocial domains (Cook et al, 2014;Sesma et al, 2008). Otero et al (2014) found that different types of interventions were most appropriate at different stages of development.…”
Section: Systematic Review Of Effective Crt Treatmentsmentioning
confidence: 99%
“…Individuals who learn only memory strategies do not necessarily show significant improvements in these areas (Cook, 2014). Improving reasoning skills also transfers to an injured child's academic performance (Sesma et al, 2008). Because children spend a majority of their time in school, the academic setting therefore provides the most opportunities for rehabilitation.…”
Section: Cognitive Interventionsmentioning
confidence: 99%